Accumulation and Migration of Phosphate Applied as Rock Phosphate in an Oil Palm Plantation - Abdul Rahman, Zaharah; Jaafar, Hawa; Abdul Hamid, Sharifuddin (1985)
An experiment was conducted to study the accumulation and migration of P applied as Christmas Island Rock Phosphate (15% P) to an oil palm crop grown on Kuala Brang soil series (Typic Paleudult). These oil palm trees were fertilized for 17 consecutive years at the rate of 0, 44 and 88 kg P/ha/year. Most of the P was found to accumulate mainly in the top 10 cm of the soil and were present in the order of Ca-P > Fe-P > Al-P. Olsen extractable P, total P, inorganic P fractions, soil CEC and pH were found to increase with increasing rates of P applied.